Evaluasi Performa Panel Surya Terintegrasi Bangunan berdasarkan Standar Greenship: Menuju Bangunan Sekolah Net Zero Energi - Susan Susan; Dyah Kusuma Wardhani; Yusuf Ariyanto; Daniel Martomanggolo Wonohadidjojo; Eric Harianto (EMARA: Indonesian Journal of Architecture, 2022)
generated from a variety of sources, both renewable and nonrenewable. Switching from nonrenewable to renewable energy sources is one of many strategies that can be used to achieve net-zero buildings. In Indonesia, this strategy is very feasible due to its abundant renewable energy resources, particularly solar energy. This research presents a school building as the proposed case. The school, SCK Citra Garden, is chosen as the pilot project due to its access to solar radiation and its minimum shading conditions. Using Helioscope software, BIPV modelling was simulated on its roof, and the electrical energy output from BIPV was calculated. The substitution percentages of BIPV energy output for conventional electrical energy consumed by the building were then measured. This percentage was compared to the National Energy Mix target and Greenhouse Gas Standard to assess its performance towards net-zero school buildings. The result shows that BIPV has a good performance. Even though the substitution percentage is still below the national energy mix target, it exceeds the greenhouse gas standard target for on-site renewable energy tools.